Five-Year Outbreak of Community- and Hospital-Acquired Mycobacterium porcinum Infections Related to Public Water Supplies - Brown-Elliott, Barbara A. (American Society for Microbiology, 2011)

(untitled)
Mycobacterium porcinum is a rarely encountered rapidly growing Mycobacterium (RGM). We identified M. porcinum from 24 patients at a Galveston university hospital (University of Texas Medical Branch) over a 5-year period. M. porcinum was considered a pathogen in 11 (46%) of 24 infected patients, including 4 patients with community-acquired disease. Retrospective patient data were collected, and water samples were cultured. Molecular analysis of water isolates, clustered clinical isolates, and 15 unrelated control strains of M. porcinum was performed. Among samples of hospital ice and tap water, 63% were positive for RGM, 50% of which were M. porcinum. Among samples of water from the city of Galveston, four of five households (80%) were positive for M. porcinum. By pulsed-field gel electrophoresis (PFGE), 8 of 10 environmental M. porcinum were determined to belong to two closely related clones. A total of 26 of 29 clinical isolates subjected to PFGE (including isolates from all positive patients) were clonal with the water patterns, including patients with community-acquired disease. Fifteen control strains of M. porcinum had unique profiles. Sequencing of hsp65, recA, and rpoB revealed the PFGE outbreak clones to have identical sequences, while unrelated strains exhibited multiple sequence variants. M. porcinum from 22 (92%) of 24 patients were clonal, matched hospital- and household water-acquired isolates, and differed from epidemiologically unrelated strains. M. porcinum can be a drinking water contaminant, serve as a long-term reservoir (years) for patient contamination (especially sputum), and be a source of clinical disease. This study expands concern about public health issues regarding nontuberculous mycobacteria. Multilocus gene sequencing helped define clonal populations.